Active Immunotherapy of Breast Cancer Treatment - Desi Dwirosalia NS (Universitas Negeri Gorontalo, 2022)
Immunotherapy as a specific moleculer targeted therapy could modulate immune respons through cytotoxic CD8+ pathway so that generate anti-tumor activity on breast cancer. HER2/Neu is the one of tumor associated antigen which extensively studied to reduce cancer progression. CTLA-4 has important role in immune checkpoint blockade that it is used for studying breast cancer either in early or advanced level. In this review, we discussed principle of immunotherapy in tumor microenvironment and some kinds of active immunotherapies, which included cancer vaccination and immune checkpoint blockade. Majority of those immunotherapies are ongoing clinical trial. Hence, this becomes a promising new field in breast cancer therapies in a future and will ultimately change the current status of breast cancer therapies.